If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + 45 = 885 Reorder the terms: 45 + 20x = 885 Solving 45 + 20x = 885 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + 20x = 885 + -45 Combine like terms: 45 + -45 = 0 0 + 20x = 885 + -45 20x = 885 + -45 Combine like terms: 885 + -45 = 840 20x = 840 Divide each side by '20'. x = 42 Simplifying x = 42
| 1=x+7/2 | | (2/3a)(2/a^2) | | -14r+19=303 | | 14x+3=45 | | 12-(k+3)=10 | | 4a-7=2a+1 | | -0.10(19)+0.40x=0.05(x-10) | | 3*(x+20)= | | 4r-2=24 | | c=48-12 | | X^2+1.75x-7.25=0 | | 3n-5=n+8 | | 5*(x+5)= | | (10x^3-19x^2-2x+12)/(2x-3) | | 1+x+3x=29 | | X^2+1.75-7.25=0 | | 6(x+2)=-6 | | 25+3.25p=60.75 | | 2x+29=53 | | 15m^2+4m=0 | | 6x(3)=75 | | k^2+14k+24=0 | | 5x^3/(7x^3+x^4) | | 9x+17=44 | | 4x-8/x^2-2x | | 25+3.25=60.75 | | x/(4x+x^2) | | 4x-25=55 | | -4(1-4a)=-5 | | 7x-25=136 | | 9x-(6x+4)=4x-33 | | 4(x-3)=7x+3 |